Discrete Event System Specification for IoT Applications - Iman Alavi Fazel; Gabriel Wainer (Sensors)
The Internet of Things (IoT) has emerged as a transformative technology with a variety of applications across various industries. However, the development of IoT systems is hindered by challenges such as interoperability, system complexity, and the need for streamlined development and maintenance processes. In this study, we introduce a robust architecture grounded in discrete event system specification (DEVS) as a model-driven development solution to overcome these obstacles. Our proposed architecture utilizes the publish/subscribe paradigm, and it also adds to the robustness of the proposed solution with the incorporation of the Brooks–Iyengar algorithm to enhance fault tolerance against unreliable sensor readings. We detail the DEVS specification that is used to define this architecture and validate its effectiveness through a detailed home automation case study that integrates multiple sensors and actuators.